Open Letters : Russian Popular Culture and the Picture Postcard, 1880-1922 - Rowley, Alison (Book collections on Project MUSE., 2013)
In Open Letters, the most comprehensive study of Russian picture postcards to date, Alison Rowley uses this medium to explore a variety of aspects of Russian popular culture.